Prevalence of Helicobacter pylori in endoscopists - (:unkn) unknown (My University, 1997)
Objective: Fecal-oral spread is the proposed route of transmission of Helicobacter pylori (H pylori) infection in humans. Endoscopy staff are at higher risk of acquisition of H pylori infection by body exposure to secretions via contaminated endoscopes. The objective of this study was to determine the prevalence of H pylori seropositivity among the doctors, nurses and staff working in various endoscopy units in Istanbul. Methods: Twenty-two endoscopists and nurses were entered into the study. Eighteen intensive care unit (ICU) nurses, 22 administrative personnel from the hospital and 22 healthy volunteers served as controls. IgG antibodies against H pylori were determined by ELISA. Results: Nineteen of 22 (86.4%) endoscopists and nurses, 13 of 18 (72.2%) ICU nurses, 14 of 22 (63.7%) administrative staff, 14 of 22 (63.7%) healthy controls were seropositive for H pylori antibodies. There was no statistically significant difference between H pylori antibody prevalence in the four groups. Moreover, no correlation was noted between H pylori prevalence and the number of endoscopic procedures, the duration of exposure, peptic ulcer history or dyspeptic complaints. Conclusion: In an area of high H pylori endemicity, where acquisition occurs at a relatively earlier age neither endoscopy nor ICU care seem to increase the acquisition of H pylori by close contact with patients.
Keywords: Endoscopy; H pylori antibodies; Helicobacter pylori